SISTEM INFORMASI MANAJEMEN DAN AKUNTANSI BARANG MILIK NEGARA PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN DAERAH PROVINSI SULAWESI UTARA - Wirananda, I Gusti Agung Sri (Universitas Sam Ratulangi, 2020)
Administration of state-owned goods is one of the important activities to account for the use of the state budget. In its implementation, BMN administration activities are supported by the implementation of the SIMAK-BMN application which functions to assist in the preparation of balance sheets and reports on state property. As the agency authorized to administer/and or use BMN at the UAKPB level, the Regional Industry and Trade Office of North Sulawesi Province must administer BMN referring to PMK No. 181/PMK.06/2016 concerning Administration of BMN to produce accurate recording and reporting of state assets. In addition, by combining information systems, proper administration procedures, and accuracy in running the system, it is hoped that errors in the BMN administration process such as human errors can be minimized.